In ovo model in cancer research and tumor immunology - Miebach, Lea; Berner, Julia; Bekeschus, Sander (Frontiers in Immunology, 2022)
Considering cancer not only as malignant cells on their own but as a complex disease in which tumor cells interact and communicate with their microenvironment has motivated the establishment of clinically relevant 3D models in past years. Technological advances gave rise to novel bioengineered models, improved organoid systems, and microfabrication approaches, increasing scientific importance in preclinical research. Notwithstanding, mammalian in vivo models remain closest to mimic the patient's situation but are limited by cost, time, and ethical constraints. Herein, the in ovo model bridges the gap as an advanced model for basic and translational cancer research without the need for ethical approval. With the avian embryo being a naturally immunodeficient host, tumor cells and primary tissues can be engrafted on the vascularized chorioallantoic membrane (CAM) with high efficiencies regardless of species-specific restrictions. The extraembryonic membranes are connected to the embryo through a continuous circulatory system, readily accessible for manipulation or longitudinal monitoring of tumor growth, metastasis, angiogenesis, and matrix remodeling. However, its applicability in immunoncological research is largely underexplored. Dual engrafting of malignant and immune cells could provide a platform to study tumor-immune cell interactions in a complex, heterogenic and dynamic microenvironment with high reproducibility. With some caveats to keep in mind, versatile methods for in and ex ovo monitoring of cellular and molecular dynamics already established in ovo are applicable alike. In this view, the present review aims to emphasize and discuss opportunities and limitations of the chicken embryo model for pre-clinical research in cancer and cancer immunology.